Calcium-dependent phosphorylation of Plasmodium falciparum serine repeat antigen 5 triggers merozoite egress - Iyer, Gayatri R. (J Biol Chem, 2018)
The human malaria parasite Plasmodium falciparum proliferates in red blood cells following repeated cycles of invasion, multiplication, and egress. P. falciparum serine repeat antigen 5 (PfSERA5), a putative serine protease, plays an important role in merozoite egress. However, regulation of its activity leading to merozoite egress is poorly understood. In this study, we show that PfSERA5 undergoes phosphorylation prior to merozoite egress. Immunoprecipitation of parasite lysates using anti-PfSERA5 serum followed by MS analysis identified calcium-dependent protein kinase 1 (PfCDPK1) as an interacting kinase. Association of PfSERA5 with PfCDPK1 was corroborated by co-sedimentation, co-immunoprecipitation, and co-immunolocalization analyses. Interestingly, PfCDPK1 phosphorylated PfSERA5 in vitro in the presence of Ca(2+) and enhanced its proteolytic activity. A PfCDPK1 inhibitor, purfalcamine, blocked the phosphorylation and activation of PfSERA5 both in vitroas well as in schizonts, which, in turn, blocked merozoite egress. Together, these results suggest that phosphorylation of PfSERA5 by PfCDPK1 following a rise in cytosolic Ca(2+) levels activates its proteolytic activity to trigger merozoite egress.